Annotation of fixed Multiword Expressions (MWEs) in a Portuguese Universal Dependencies (UD) treebank: Gathering candidates from three different sources - de Souza, Elvis; Freitas, Cláudia (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2023)
Delimiting and correctly annotating multiword expressions (MWEs) is an important task in constructing a gold standard treebank. In this paper, we applied three methods to the PetroGold corpus to identify MWE candidates. The methods include (1) leveraging expressions previously identified by the PALAVRAS annotator, (2) statistical analysis of collocations in Petroles, a larger non-annotated corpus, and (3) a curated list of co-occurring words from the POeTiSA project. Through extensive filtering and alignment with Universal Dependencies (UD) guidelines, we revised the annotations of 2,467 MWEs in the PetroGold corpus, we tested a new annotation for the part-of-speech (POS) of the words that are part of MWEs and we provide two computationally readable resources to assist other annotators.